VOX POPULI - PARADIGM OF CONTEMPORARY LAW - Oana Andra NIȚĂ (Challenges of the Knowledge Society)
In the contemporary society, which tends to be more and more close to uniformity and globalization, law tends to harmonize the individual interests with the general one. Social life is guided by all the norms imposed on individuals and collectives, which in some particular cases may be applied even through the coercion of the state. Public institutions and democratic societies live through the coexistence and cooperation of their members. As long as the constituent elements of the societies are represented by individuals, each of them must also comply with the coexistence and cooperation rules necessary to maintain the balance of the rule of law. As a society, we need justice, but it is not necessary for people to get tired of pretending justice to be done. Meanwhile, there is a need for a different justice, with a true culture of law and with strong liability. Lately worldwide events, such as great protests with high impact over national administrative and legal systems, as well as over international political relations have proved to be a massive arm against the entry into force of normative acts. The purpose of the paper and the objectives pursued by us will try to reveal whereas the initiatives of the people in their entirety, and not as individuals, are legally solid and if the role of such events is positive or it will only end in destabilizing the rule of law